Impact of an online writing aid tool for writing a randomized trial report: the COBWEB (Consort-based WEB tool) randomized controlled trial. - Barnes, C; Boutron, I; Giraudeau, N; Porcher, R; Altman, D; Ravaud, P (BioMed Central, 2015)
BACKGROUND: Incomplete reporting is a frequent waste in research. Our aim was to evaluate the impact of a writing aid tool (WAT) based on the CONSORT statement and its extension for non-pharmacologic treatments on the completeness of reporting of randomized controlled trials (RCTs). METHODS: We performed a 'split-manuscript' RCT with blinded outcome assessment. Participants were masters and doctoral students in public health. They were asked to write, over a 4-hour period, the methods section of a manuscript based on a real RCT protocol, with a different protocol provided to each participant. Methods sections were divided into six different domains: 'trial design', 'randomization', 'blinding', 'participants', 'interventions', and 'outcomes'. Participants had to draft all six domains with access to the WAT for a random three of six domains. The random sequence was computer-generated and concealed. For each domain, the WAT comprised reminders of the corresponding CONSORT item(s), bullet points detailing all the key elements to be reported, and examples of good reporting. The control intervention consisted of no reminders. The primary outcome was the mean global score for completeness of reporting (scale 0-10) for all domains written with or without the WAT. RESULTS: Forty-one participants wrote 41 different manuscripts of RCT methods sections, corresponding to 246 domains (six for each of the 41 protocols). All domains were analyzed. For the primary outcome, the mean (SD) global score for completeness of reporting was higher with than without use of the WAT: 7.1 (1.2) versus 5.0 (1.6), with a mean (95 % CI) difference 2.1 (1.5-2.7; P <0.01). Completeness of reporting was significantly higher with the WAT for all domains except for blinding and outcomes. CONCLUSION: Use of the WAT could improve the completeness of manuscripts reporting the results of RCTs. TRIAL REGISTRATION: Clinicaltrials.gov ( http://clinicaltrials.gov NCT02127567 , registration date first received April 29, 2014).